Parallel stent grafts for the treatment of complex aortic aneurysms: A single center study. (October 2018) - Silverberg, Daniel; Rimon, Uri; Raskin, Daniel; BarDayan, Avner; Halak, Moshe
Background: "Chimney" techniques with parallel grafts used in order to extend the landing zones in endovascular aneurysm repair (ch-EVAR) are increasingly being reported. Conflicting data has been reported regarding the success and durability of the repair. We report a single center experience using ch-EVAR in treating complex aortic pathologies. Methods: We performed a retrospective review of all patients treated with ch-EVAR in our institution between 2013 and 2017. Data collected included patients demographics, indications for surgery, configuration of parallel grafts, technical success, and perioperative morbidity and mortality. Follow-up data included aortic sac size, reintervention rate, and overall mortality. Results: Thirty-five patients underwent treatment of their aneurysms with parallel grafts. Sixty parallel grafts were placed. Mean age was 75 years (range 59–93) and 30 (85%) were male. Technical success was achieved in 32 (91%) patients. Mean follow up was 12 months. Sac size decreased in diameter or remained unchanged in 26 of the 30 (86.6%) patients. Four patients were found to have enlarging aneurysms due to gutter endoleaks. All were treated successfully with endovascular methods. The estimated primary patency was 95% at 12 months. Probability of freedom from intervention was 75% at 12 months. No late aneurysm related mortality occurred. Conclusion: The use of ch-EVAR in treating complex aortic aneurysms is technically feasible and safe. Gutter endoleaks are encountered only in a minority of the cases, and can be treated with minimally invasive techniques. Longer term follow up is required to evaluate the patency of these parallel grafts and the durability of the aneurysm exclusion.